2018
DOI: 10.1104/pp.18.01067
|View full text |Cite
|
Sign up to set email alerts
|

Phytoparasitic Nematode Control of Plant Hormone Pathways

Abstract: G.G. and M.G.M. conceived the structure and the contents of the paper. G.G. wrote the plant hormone part and M.G.M. focused on the effector part. G.G. and M.G.M. commented on and edited the final text. [OPEN] Articles can be viewed without a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
115
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(117 citation statements)
references
References 141 publications
1
115
0
1
Order By: Relevance
“…TIR, LAX1) ( Fig 7C and 421 S5 Table). It has been recently reported that nematode invasion results in induced auxin 422 biosynthesis and responsive genes while genes encoding for repressors are switched off 423 (Gheysen & Mitchum, 2018). Similar to this scenario, in our dataset, auxin repressors were 424 repressed further highlighting the importance of auxin manipulation in nematode parasitism.…”
Section: Development 368supporting
confidence: 79%
See 2 more Smart Citations
“…TIR, LAX1) ( Fig 7C and 421 S5 Table). It has been recently reported that nematode invasion results in induced auxin 422 biosynthesis and responsive genes while genes encoding for repressors are switched off 423 (Gheysen & Mitchum, 2018). Similar to this scenario, in our dataset, auxin repressors were 424 repressed further highlighting the importance of auxin manipulation in nematode parasitism.…”
Section: Development 368supporting
confidence: 79%
“…Cytokinin and auxin hormones have been implicated in the induction and development of NFS 428 (Gheysen & Mitchum, 2018). In the present study, genes involved in CK signaling pathway 429 were differentially expressed.…”
Section: Gcs 427mentioning
confidence: 53%
See 1 more Smart Citation
“…Since the root phenotypes of rice d mutants do not seem to be at the basis of their increased M. graminicola resistance, we hypothesized that altered defense hormones might be involved. Plant hormones, especially JA-mediated defense signaling, play an important role in both monocot and dicot plant species to protect against root-knot nematode infections (Cooper et al, 2005;Nahar et al, 2011;Gheysen & Mitchum, 2019). It was shown that the JA-precursor cis-OPDA also acts as a key signaling molecule in the regulation of Arabidopsis defense against the root-knot nematode M. hapla (Gleason et al, 2016).…”
Section: New Phytologistmentioning
confidence: 99%
“…simultaneously influence plant cell differentiation and modulate the defense responses to establish a successful infection via feeding cell formation (Gheysen & Mitchum, 2011;Ji et al, 2013). The plant hormones JA, ethylene, SA, ABA, brassinosteroids (BR), gibberellic acid (GA), and auxin are known to be involved in the interactions between plant and root-knot nematodes (Karczmarek et al, 2004;Nahar et al, 2011Nahar et al, , 2013Kyndt et al, 2017;Yimer et al, 2018;Gheysen & Mitchum, 2019). For instance, the JA-based defense pathway plays a vital role in rice defense against M. graminicola infection, whereas SA is also involved in defense but to a lesser extent than JA (Nahar et al, 2011).…”
Section: Introductionmentioning
confidence: 99%